OPTIMALISASI PORTAL RUMAH BELAJAR KEMENDIKBUD DI MASA PANDEMI - Dewi Muliasari; Tino Feri Efendi (JURNAL ILMIAH EDUNOMIKA, 2022)
This research is a qualitative research using a type of phenomenology. This study aims to describe the use of the Ministry of Education and Culture's Learning House Portal in the learning process at Vocational High Schools. The sampling technique used in this study was purposive sampling using the research subjects as teachers who had used the Ministry of Education and Culture's Learning House Portal in the learning process in class. The data collection technique used was through observation, containing the impact of learning observations and teacher interviews regarding the use of the learning house portal, learning activities and steps taken by teachers in utilizing the Ministry of Education and Culture learning home portal as an online learning model in Vocational High Schools. The research was conducted in the State Vocational High School 3 Sukoharjo. the impact of the research shows that the learning steps carried out by the teacher in utilizing the Ministry of Education and Culture's Learning House portal are started based on the preparation and implementation of learning which contains the opening activities, the core and the epilogue of learning. Some of the features that teachers have used in learning are learning resources, electronic school books (BSE), and question banks. The methods used by teachers in utilizing the learning home portal as an example of online learning during the learning process can be grouped into (1) Presentations/Demonstrations, (2) Small group discussions & (3) Individual Learning. Keywords : Optimization, Portals, Learning Models, Online